Densa tessitura: uma leitura em contraponto, a visão da academia sobre a produção literária de Marina Colasanti - Miguel, Maria Aparecida de Fátima [UNESP] (2015)
Although Marina Colasanti (1937) is considered by the critics as one of the exponents of Brazilian children and youthful literature, and having her production, in this segment, published since the outset 1980s until this moment, still is very unsystematic the study of literary criticism on the writer's work. This work takes as object a significant sample of academic production about the literary production of the writer, leaning on dissertations and on theses that analyze the Children's and the youthful work of Marina Colasanti, as those that turn to literary texts that have been priority addressed to adult readers, considering that, sometimes, these two literary universes are shown merged. Twenty academic papers constitute the corpus of this work, it has been identified through the database Capes and the query at physical and virtual libraries of various universities. From a methodological point of view, the corpus received a homogeneous treatment for data collection, have been subjected to a grid (or "chart") compose of 15 different categories that guided the study of each thesis or dissertation. That systematic analysis propitiated, as research results, concludes in a kind of balance on the critical fortune, being possible sight four main topics that concern to the critical studies on the work of Marina Colasanti, according to different theoretical perspectives: the female specific; the myth; the poetic language; and the love.